Early-Onset Alzheimer’s Disease Masquerading as Catatonia - Aljoharah Alakkas; Aaron Meyer; Eric Debbold; Raisa Yagudayeva; Jonathan Bui (Case Reports in Neurological Medicine)
A 35-year-old woman with a history of sexual trauma was brought in by her family for further evaluation of depressive symptoms and progressive decline in activities of daily living. She was admitted to the inpatient psychiatric unit for the treatment of suspected catatonia. After failure to respond to standard medical treatment, she received an extensive workup, which ultimately revealed a PSEN1 mutation consistent with early-onset Alzheimer’s disease. Diagnosis was challenging because of her young age, lack of reliable family history, and reports of recent sexual abuse by her biological father. This case is a cautionary reminder for clinicians that end stages of dementia can present similar to catatonia with mutism, lack of spontaneous movement, and refusal to eat. The clues to the diagnosis were profound cortical atrophy and lack of improvement with optimal medical management.